2006
DOI: 10.1364/ol.31.003492
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation in thermally poled chalcohalide glass

Abstract: Second-harmonic generation in 60GeS(2)-20Ga(2)S(3)-20KBr chalcohalide glass was investigated by the thermal poling method. A large second-order nonlinear susceptibility, as high as 7.0 pm/V, was obtained in a poled sample by Maker fringe analysis. We believe this to be the first time that a clear second-harmonic wave was observed in chalcohalide glasses containing large amount of alkali ions (6.25 at. %). Such observation is of great potential use in all optical waveguide devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It was successfully applied on few chalcogenide glasses, showing some of the most efficient second-order optical responses in glassy materials. The best results were obtained by Guignard et al and Jing et al 59,60 who have respectively obtained efficient v (2) of 8 pm/V and 7 pm/V in the Ge 25 Sb 10 S 65 glass and the 60GeS 2 -20Ga 2 S 3 -20 KBr chalcohalide composition. However, it has been clearly demonstrated that the key point for poled chalcogenide materials concerns the stability in time of their secondorder optical response.…”
Section: High-v (3) Glasses To Optimize the Sonl Responsementioning
confidence: 95%
See 3 more Smart Citations
“…It was successfully applied on few chalcogenide glasses, showing some of the most efficient second-order optical responses in glassy materials. The best results were obtained by Guignard et al and Jing et al 59,60 who have respectively obtained efficient v (2) of 8 pm/V and 7 pm/V in the Ge 25 Sb 10 S 65 glass and the 60GeS 2 -20Ga 2 S 3 -20 KBr chalcohalide composition. However, it has been clearly demonstrated that the key point for poled chalcogenide materials concerns the stability in time of their secondorder optical response.…”
Section: High-v (3) Glasses To Optimize the Sonl Responsementioning
confidence: 95%
“…The best results were obtained by Guignard et al . and Jing et al . who have respectively obtained efficient χ (2) of 8 pm/V and 7 pm/V in the Ge 25 Sb 10 S 65 glass and the 60GeS 2 –20Ga 2 S 3 –20 KBr chalcohalide composition.…”
Section: Thermally Poled Glasses: Progress Toward Photonic Applicatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Another major part of the story is the temporal stability of the SHG, which varies greatly for materials such as silica and other oxide glasses, and also in the focus of this study, chalcogenide glasses (ChGs). Specifically in poled chalcogenide glasses, the temporal stability varies widely in the literature [10,12].…”
Section: Introductionmentioning
confidence: 99%